(untitled) (Czech Journal of International Relations, 2012)
The paper analyses the international debate that concerns the efforts to create an effective control framework for the illicit arms trade and its impact on global peace and international security. The conventional arms trade is a wide spreading phenomenon that negatively affects many countries and regions all around the world. Unlike in the case of the trade of technologies and materials that could potentially be used in chemical, biological, or nuclear weapons, there are no comprehensive, global controls on the international trade in conventional arms (although some regional and multilateral frameworks have been developed for it). The Arms Trade Treaty (ATT) is thus a response to the appeals of governments, nongovernmental organizations and individuals that seek to create a regulatory mechanism for conventional arms in the international environment. The paper tries to identify the main patterns of the discussion, the proponents, the opponents and the arguments that have defined the debate in the last decade.